Reparative justice, environmental crime and penalties for the powerful - White, R. D. (Crime, law and social change, 2017)
Environmental harms are frequently part and parcel of ordinary commercial practice. Powerful social interests not only perpetuate great harms, they also obscure and mask the nature of the harm production. They are also best placed to resist the criminalisation process generally. Indeed, when it comes to corporate criminality, recidivism is built-in to the endeavour to the extent that payment of fines is construed as simply part of the cost of doing business (whether related to processing and transferring of waste, or cutting down trees in particular sections of the forest). Unless substantial penalties are put into play, there is little deterrent. This paper proposes that reparative justice, with an emphasis on repairing harm within a generally more punitive context, would be more appropriate and effective. This is illustrated by consideration of recent cases heard in the New South Wales Land and Environment Court in which a number of private companies were penalised using an interesting variety of sanctions. Repairing harm should not be conflated with 'restorative justice' per se. This is important, since 'repairing harm' can be imposed upon offenders (especially corporate offenders) without necessarily involving consensual agreement and/or 'conferencing' methods of negotiation. Company personnel, including senior managers, change. But to change company practices, especially those that pertain to the economic profit margin, requires regulatory and enforcement systems that penalise and sanction in ways that are tailored to the size and activities of the corporation. For this to succeed, it is argued that specialist environmental courts with well developed problem-solving skills and capacities are required.